The Brain Development and Nutrition - Anzalman; Thaheransyah; Hakim, Rosniati; Dahlan, Dasrizal; Lahmi, Ahmad (The Future of Education Journal, 2025)
Brain development is a complex process that begins during fetal development and continues throughout life. Nutrition plays a crucial role in brain development, especially during the early stages of life. Adequate nutrition, including omega-3 fatty acids, proteins, vitamins, and minerals, supports neuron formation, myelination, and synaptogenesis, which affect cognitive function. Deficiencies in essential nutrients such as iron, folic acid, and vitamin D during growth can hinder brain development and lead to cognitive and behavioral problems later in life. This article discusses the relationship between nutrition and brain development, as well as the importance of a balanced diet during growth to achieve optimal brain function. The findings emphasize the need for increased attention to nutritional needs from pregnancy through early childhood as a preventive measure to improve children's health and cognitive development.